METAFORA PADA IKLAN LAYANAN MASYARAKAT COVID-19 - Sri Nurbani; Yelly Andriani Barlian (STKIP Siliwangi, 2022)
Campaigns regarding Covid-19 outbreak are now being intensively carried out by the government. Public Service Advertisements (PSA) are also one of the spearheads to reduce the spread of Covid-19. This phenomenon has attracted the author's attention to examine the metaphor in PSA as a creative strategy carried out by advertisers to convey their message. The purpose of this study is to reveal conceptual metaphors in the Covid-19 PSA which can later be used as a reference in making advertisements related to Covid-19, also to provide understanding to readers through headline about Covid-19 by involving conceptual metaphors which are expected to be effective accepted by the public or readers. This study uses qualitative methods used to reveal social conditions that occur in the community. The findings of this study: there are two types of metaphorical concepts in the Covid-19 Headline, namely structural and ontological types, the most dominant is the ontological type, while the meanings built are atropomorphic metaphors, animal metaphors, metaphors from concrete to abstract, and synesthesia metaphors. These findings can be used as recommendations for advertisers in designing creative strategies related to Covid-19 advertisements so that their advertisements are effective and easily digested by the target audience or readers.